ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA BANK RAKYAT INDONESIA KANTOR CABANG BENGKULU - -, Khaidir; Susanti, Neri (JURNAL EKOMBIS REVIEW, 2015)
Khaidir, Neri Susanti; The research objective to factors determine the performance of accounting information systems at Bank Rakyat Indonesia Branch Office of Bengkulu. This study is a descriptive study, with a sample are employees of Bank Rakyat Indonesia Branch Office Bengkulu wear or use of accounting information systems as much as 42 employees. Methods of data collection done by survey method, while data analysis using rating scale analysis.The results reveal that the most dominant factor affecting the performance of accounting information systems at Bank Rakyat Indonesia Branch Office Bengkulu end user satisfaction factor is an average of 176, the second factor is the education and training programs by an average of 173, the next factor is the support of top management an average of 168 and the last factor is the ability of a personal technique average of 165.Key Word: Performance, Accounting Information Systems